Rituximab monotherapy versus glucocorticoid therapy for adult minimal change disease: a retrospective study on noninferiority - Li, Xiaoyun; Yao, Guoxiang; Sun, Yujiao; Li, Na; Gao, Caifeng; Wang, Haiping; Wang, Rong; Chen, Bing (Frontiers in Nephrology, 2025)
IntroductionTo verify whether rituximab (RTX) monotherapy is noninferior to glucocorticoids in inducing and maintaining remission in adults with minimal change disease (MCD).MethodWe retrospectively analyzed the clinical data of 60 patients with minimal change disease (MCD) who were diagnosed with MCD by renal pathology biopsy and electron microscopy before their first visit to the Department of Nephrology of Shandong Provincial Hospital between 01/2020 and 01/2024, and were diagnosed with MCD at the first visit without acute kidney injury (AKI). Patients were divided into a RTX treatment group (RTX group, 20 cases) and glucocorticoids (GC) treatment group (GC group, 40 cases). None of the patients had previously received steroid/immunosuppressive therapy. The RTX group received rituximab monotherapy. At the 6-month follow-up, the RTX group received additional rituximab infusions as maintenance therapy. The primary endpoints were the time to induced remission, 12-month remission, and relapse rates in each group; the secondary endpoints were the safety and incidence of side effects.ResultsAfter treatment during the 12-month follow-up period, 57 out of 60 patients (95%) achieved remission, of which 48 (80%) achieved complete remission; and 9 (15%) patients relapsed during the follow-up period. A total of 24 (40%) patients experienced adverse events while receiving treatment. 19 (95%) patients in the RTX group and 38 (95%) patients in the GC group achieved remission within 12 months of follow-up, respectively [the difference in rates between the two groups was 0%, 95% confidence interval (0.08, 11.73)]. In the RTX group, 14 (70%) achieved complete remission. In the GC group, 34 (85%) achieved complete remission (p=0.304). In the RTX group, 2 (10%) patients relapsed, and in the GC group 7 (18%) patients relapsed (p=0.701). 1 (5%) patient in the RTX group and 23 (58%) patients in the GC group experienced adverse events (p=0.000), none of which were severe.ConclusionAdequate RTX monotherapy is noninferior to adequate glucocorticoids in inducing and maintaining remission in adult MCD patients without AKI, with fewer adverse effects and better adherence, and may be considered as a first-line treatment option for adult MCD patients without AKI.